Boron based nanosheets as reducing templates in aqueous solutions: towards novel nanohybrids with gold nanoparticles and graphene. Issue 44 (5th November 2018) - James, Asha Liza; Khandelwal, Shikha; Dutta, Arnab; Jasuja, Kabeer
Abstract : Boron based nanosheets act as chemically reducing templates in aqueous solution to form mixed-dimensional heterostructures with gold nanoparticles and graphene. Abstract : We show that nanosheets obtained by exfoliating magnesium diboride bear an intrinsic ability to elicit chemical reduction of quinone-based molecules. They also reduce gold salt into ultra-small gold nanoparticles and graphene oxide into reduced graphene oxide. These nanosheets subsequently interface with the partner nanomaterial in solution to form novel nanohybrids.